Reaction blueprints and logical control flow for parallelized chiral synthesis in the Chemputer - Šiaučiulis, Mindaugas; Knittl-Frank, Christian; M. Mehr, S. Hessam; Clarke, Emma; Cronin, Leroy (Nature communications, 2024)
Despite recent proliferation of programmable robotic chemistry hardware, current chemical programming ontologies lack essential structured programming constructs like variables, functions, and loops. Herein we present an integration of these concepts into χDL, a universal high-level chemical programming language executable in the Chemputer. To achieve this, we introduce reaction blueprints as a chemical analog to functions in computer science, allowing to apply sets of synthesis operations to different reagents and conditions. We further expand χDL with logical operation queues and iteration via pattern matching. The combination of these new features allows encoding of chemical syntheses in generalized, reproducible, and parallelized digital workflows rather than opaque and entangled single-step operations. This is showcased by synthesizing chiral diarylprolinol catalysts and subsequently utilizing them in various synthetic transformations (13 separate automated runs affording 3 organocatalysts and 12 distinct enantioenriched products in 42–97% yield, up to > 99:1 er), including automated catalyst recycling and reuse. Current chemical automation ontologies are disconnected from essential structured programming constructs such as variables, functions, and loops. Herein the authors present an approach to translating computer science concepts to first-class primitives within a universal high-level chemical programming language executable in the Chemputer.